Dosing regimens, FVIII levels and estimated haemostatic protection with special focus on rFVIIIFc. (11th February 2016) - Berntorp, E.; Negrier, C.; Gozzi, P.; Blaas, P‐M.; Lethagen, S.
Introduction: Aim: To use Pharmacokinetic (PK) simulations to illustrate potential differences in clinical outcomes between prophylaxis with conventional recombinant factor VIII (rFVIII) and rFVIIIFc, an extended half‐life rFVIII covalently fused to the Fc domain of human IgG1. Methods: Population PK estimates from 180 (rFVIIIFc) and 46 (rFVIII) severe haemophilia A patients were used to simulate FVIII activity over time at various rFVIIIFc dosing regimens compared to rFVIII 30 IU kg −1 three times weekly in a typical adult patient. Results: rFVIII dosed 3x30 IU kg −1 weekly gave trough levels of 2.7, 2.8 and 0.7 IU dL −1, and time spent below 1, 3 and 5 IU dL −1 of 0.2/1.2/2.3 days week −1 . rFVIIIFc 2 x 45 IU kg −1 gave higher troughs (4.4 and 1.7 IU dL −1 ) and shorter time spent below 1, 3 and 5 IU dL −1 (0/0.6/1.3 days week −1 ), with same total factor consumption. rFVIIIFc 2 x 30 IU kg −1 gave similar troughs (3.0 and 1.2 IU kg −1 ) and time spent below 1, 3 and 5 IU dL −1 (0/1.0/2.1 days week −1 ), despite total factor consumption being reduced by one‐third. The same dose and interval of rFVIIIFc (3 x 30 IU kg −1 ) gave substantially higher troughs (7.8, 8.5 and 3.3 IU dL −1 ) and markedly shorter time spent below 1, 3 and 5 IU dL −1 (0/0/0.4 days week −1 ). Conclusion: The lower clearance of rFVIIIFc compared to conventional rFVIII gives rFVIIIFc the potential of improved bleed prevention and reduced injection frequency at similar factor consumption. Although additional clinical data are required to confirm the conclusions, the simulations clearly show the potential of rFVIIIFc of increased flexibility to tailor treatment to the individual patient, and to advance the standard of care in haemophilia.